2016
DOI: 10.1177/0363546516677727
|View full text |Cite
|
Sign up to set email alerts
|

Joint Loading in the Sagittal Plane During Gait Is Associated With Hip Joint Abnormalities in Patients With Femoroacetabular Impingement

Abstract: Background Femoroacetabular impingement (FAI) is a morphological abnormality of the hip joint that results in functional impairments during various activities of daily living (ADL) such as walking. Purpose/Hypothesis The purpose of this study was to determine if lower extremity joint loading differed between patients with FAI and controls and to determine whether these altered biomechanical parameters were associated with intra-articular abnormalities. It was hypothesized that patients with FAI would exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 36 publications
2
32
1
Order By: Relevance
“…There was moderate evidence of no difference in peak hip torques for flexion (−0.19, 95% CI −0.54 to 0.16; I 2 =21%, P=0.28), extension (−0.25, 95% CI −0.55 to 0.06; I 2 =0%, P=0.80), abduction (−0.04, 95% CI −0.39 to 0.31; I 2 =0%, P=0.53), adduction (−0.33, 95% CI −0.71 to 0.05; I 2 =0%, P=0.37) and internal rotation (−0.25, 95% CI −0.62 to 0.13; I 2 =0%, P=0.73) (figure 2D). Additionally, one moderate-quality29 study showed insufficient evidence that patients with FAIS had a greater peak hip flexion torque impulse (0.89, 95% CI 0.25 to 1.52) and no difference in extension torque impulse (−0.49, 95% CI −1.11 to 0.12) (table 5). …”
Section: Resultsmentioning
confidence: 99%
“…There was moderate evidence of no difference in peak hip torques for flexion (−0.19, 95% CI −0.54 to 0.16; I 2 =21%, P=0.28), extension (−0.25, 95% CI −0.55 to 0.06; I 2 =0%, P=0.80), abduction (−0.04, 95% CI −0.39 to 0.31; I 2 =0%, P=0.53), adduction (−0.33, 95% CI −0.71 to 0.05; I 2 =0%, P=0.37) and internal rotation (−0.25, 95% CI −0.62 to 0.13; I 2 =0%, P=0.73) (figure 2D). Additionally, one moderate-quality29 study showed insufficient evidence that patients with FAIS had a greater peak hip flexion torque impulse (0.89, 95% CI 0.25 to 1.52) and no difference in extension torque impulse (−0.49, 95% CI −1.11 to 0.12) (table 5). …”
Section: Resultsmentioning
confidence: 99%
“…Once symptoms are improved, continuing an individualized program may be beneficial in further reducing this risk. 23,24,43 Additional treatment sessions including manual therapy and exercise, like those implemented in this case series, may be beneficial in the long-term management of athletes, as they continue to address any potential long-term impairments 14,22,32,36,63 and may improve outcomes. 57 For comparison, it is common practice for baseball pitchers to perform an individualized arm-care program in the presence of sportspecific morphological adaptations.…”
Section: Discussionmentioning
confidence: 95%
“…Common anatomical features such as posture and bony hip morphology may impact function 23,24,35,36 and potentially result in pathology. However, asymptomatic findings and concurrent pathoanatomical diagnoses make treating specific structures challenging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations